CORRELATION BETWEEN PHYSICAL ACTIVITY AND FASTING BLOOD GLUCOSE IN PATIENT WITH TYPE 2 DIABETES MELLITUS - Rani Nurvita; Djohar Nuswantoro; Jongky Hendro Prajitno (Universitas Airlangga, 2022)
Introduction: Diabetes Mellitus is a disease caused by an increase in blood glucose levels, which is an increase in levels at an abnormal level, or called hyperglycemia. Diabetes is a metabolic disease related to various factors such as physical activity, lifestyle, habits, diet, etc. Diabetes mellitus is classified as type 1 diabetes mellitus, type 2 diabetes mellitus, and gestational diabetes. Type 2 Diabetes Mellitus (T2DM) is caused by the body's inability to use insulin effectively (insulin resistance). This study aims to determine the relationship between physical activity and fasting blood glucose levels of T2DM patients to provide social change by increasing physical activity to control fasting blood glucose in patients with T2DM. Methods: This study is quantitative research of analytic observation with a cross-sectional design. The sample in this study was the outpatient T2DM at Endocrine Unit RSUD Dr Soetomo Surabaya from June until September 2018 consecutive sampling. The independent variable was physical activity, and the dependent variable was fasting blood glucose (FBG). Methods of collecting primary data by interview using IPAQ (International Physical Activity Questionnaire) and secondary data by looking at the results of FBG from the patient's medical records of laboratory tests. Collected data were entered into Microsoft excel and then statistically analyzed using IBM SPSS 22. Spearman’s Rho Correlation Test analyzed the data. Results: Sixty three respondents became in inclusion criteria. Most patients have a moderate physical activity of 28 people, or around 44.4%. Thirty-two people had poor fasting blood glucose levels of about 50.8%. The analysis result was there is a significant correlation between physical activity and fasting blood glucose levels of T2DM patients and a low correlation coefficient in the opposite direction (not in the same order). Conclusion: Physical activity impacts fasting blood glucose levels and has a negatively correlated direction. The increase in physical activity showed by the value of the IPAQ score, followed by a decrease in fasting blood glucose level.